The Integration of Dakwah in Journalism: Peace Journalism - Lecomte, Isabelle (Jurnal Komunikasi Islam, 2014)
This article discusses the integration of Islam, particularly da’wa, with peace journalism. It argues that Islamic communication is basically peace journalism. Islamic communication consists of tabligh (information), taghyir (so–cial change), khairu ummah (exemplary community), and akhlaq al-karimah (noble behavior, civil society), the purpo–se of which is to perpetuate conflict sensitivity, constructive conflict, and conflict resolution. Muslim journalists can produce articles about Islam to promote Islamic teachings relevant to universal values, including inclusiveness for humanity values which are inclusive. It is important for Muslims to create a platform for sharing information and religious values that can be discussed by audiences. Keywords: Integration of Dakwah in journalism, peace journalism ———————————————————————- Artikel ini mengulas integrasi Islam, khusunya dakwah, dengan jurnalistik damai (peace journalism). Penulis perpandangan bahwa pada dasarnya, komunikasi Islam adalah jurnalistik perdamaian (peace journalism). Sebab komunikasi Islam terdiri daripada tabligh, taghyir, khairu ummah dan akhlak al- karimah, yang bertujuan untuk membangun kepekaan sosial, perdamaian, dan resolusi konflik. Pula Peace journalism menggambarkan nilai-nilai universal dan inklusif, seperti keadilan, keamanan, kesela–matan, keharmonian, toleransi, hormat kepada semua manusia sebagaimana diajarkan oleh Islam. Oleh karennya, jurnalis Muslim dapat bekerja di media Islam dan meng–hasilkan karya-karya tulisan tentang nilai-nilai Islam yang inklusif. Hal ini penting bagi umat Islam untuk membuat platform untuk berbagi informasi dan nilai-nilai agama yang dapat didiskusikan. Kata Kunci: integrasi dakwah dalam jurnalistik, jurnalistik damai